The Gig Economy and Its Impact on Women in Iraq - Hawra Milani; Zahra Shah; Rikke Bjerg Jensen (Global Labour Journal)
The gig economy has significantly transformed Iraq’s labour market, creating new opportunities for women while also exposing persistent inequalities. This paper traces the experiences of Iraqi women in the gig economy, drawing on both individual and collective insights grounded in the authors’ work in this context. These experiences reveal the dual nature of the gig economy: providing flexible work options while perpetuating vulnerabilities such as discrimination and economic insecurity. By situating our analysis within Iraq’s unique socio-economic conditions, including women’s low workforce engagement and infrastructural challenges, we contribute to a deeper understanding of the dynamics shaping women’s participation in this emerging labour market. The paper explores the types of gig work available to Iraqi women, alongside the structural barriers they face, such as limited digital infrastructure and inadequate legal protections. We conclude by highlighting actionable pathways for improving economic outcomes for women and fostering inclusive growth in the gig economy.